Sinuous Objects Revaluing Women's Wealth in the Contemporary Pacific - Hermkens, Anna-Karina; Lepani, Katherine (ANU Press, 2017)
Some 40 years ago, Pacific anthropology was dominated by debates about 'women's wealth'. These exchanges were generated by Annette Weiner's (1976) critical reappraisal of Bronisław Malinowski's classic work on the Trobriand Islands, and her observations that women's production of 'wealth' (banana leaf bundles and skirts) for elaborate transactions in mortuary rituals occupied a central role in Trobriand matrilineal cosmology and social organisation. This volume brings the debates about women's wealth back to the fore by critically revisiting and engaging with ideas about gender and materiality, value, relationality and the social life and agency of things. The chapters, interspersed by three poems, evoke the sinuous materiality of the different objects made by women across the Pacific, and the intimate relationship between these objects of value and sensuous, gendered bodies. In the Epilogue, Professor Margaret Jolly observes how the volume also 'trace[s] a more abstract sinuosity in the movement of these things through time and place, as they coil through different regimes of value ... The eight chapters ... trace winding paths across the contemporary Pacific, from the Trobriands in Milne Bay, to Maisin, Wanigela and Korafe in Oro Province, Papua New Guinea, through the islands of Tonga to diasporic Tongan and Cook Islander communities in New Zealand'. This comparative perspective elucidates how women's wealth is defined, valued and contested in current exchanges, bride-price debates, church settings, development projects and the challenges of living in diaspora. Importantly, this reveals how women themselves preserve the different values and meanings in gift-giving and exchanges, despite processes of commodification that have resulted in the decline or replacement of 'women's wealth'.